Implemented Protocol Regarding Recombinant Tissue Plasminogen Activator Administration for Nurses: An Updated Review - Patil, Digvijay R. (Innovational: Journal of Nursing and Healthcare, 2024)
There are several thrombolytic agents in use; however, this article will focus on tissue type plasminogen activator (TPA). A thorough understanding of the benefits and risks associated with thrombolytic administration will be critical in the successful utilization of this form of therapy. Recent data show that infarct size is linked to mortality. In the 1980s, therapy for acute myocardial infarction (AMI) patients is directed at salvaging myocardium and limiting infarct size. Before this, therapy consisted mainly of supportive care that resulted only in minor effects on the patients prognosis. Intracoronary thrombus has recently been recognized as the cause in most cases of AMI. Thrombolytic therapy represents a method of dissolving a thrombus and reestablishing blood flow to the previously occluded coronary artery. Early reperfusion of ischemic myocardial tissue can limit the amount of damage caused by evolving myocardial infarction. There is a need for a standard protocol for the improvement of knowledge and practice regarding recombinant tissue plasminogen activator administration.